Hubungan Tingkat Pengetahuan Wanita Usia Subur (WUS) dan Dukungan Suami dengan Pemeriksaan Inspeksi Visual Asam Asetat (IVA) sebagai Metode Deteksi Lesi Prakanker Serviks di Puskesmas Kalibalangan Kabupaten Lampung Utara Tahun 2019 - M. Rizky Fathurrohim; Rasmi Zakiah Oktarlina; Nurul Islamy4 (Medula, 2019)
Cervical cancer is the fourth most common cancer in women with an estimated 530,000 new cases, representing 7.9% of all female cancers. Cervical cancer events can be detected by the Visual Inspection Method of Acetic Acid (IVA). The relationship between the level of knowledge of women of childbearing age and husband's support to the visual inspection of acetic acid as an early detection of cervical pre-cancerous lesions. This type of quantitative research with cross sectional design. This research has been carried out at the Kalibalangan Main Health Center. The target of this study is all women of childbearing age who have been married, a sample of 196 people with convenience sampling technique. The object taken is the husband's knowledge and support with data collection by questionnaire. Data analysis used univariate and bivariate (chi square). As many as 151 (77.0%) respondents had never had an IVA examination. Based on the results of the study, most of the respondents with poor knowledge were 121 (61.7%) and there were no husband's support around 144 (73.5%). There is a correlation between knowledge of women of childbearing age and husband's support to the Acetic Acid Visual Inspection Examination as an early detection of cervical pre-cancerous lesions in Induk Health Center, Kalibalangan Village, North Lampung Regency in 2019 (p-value 0,000 and OR 13,707).